2016
DOI: 10.1021/acs.chemmater.6b01383
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Polarization-Induced Loss Mechanisms in Polypropylene/BaTiO3 Nanocomposite Dielectrics

Abstract: Polymer/inorganic particle nanocomposites (or nanodielectrics) have attracted pronounced attention for electric energy storage applications, based on a hypothesis that polymer nanodielectrics could combine the high permittivity of nanoparticles and the high electrical breakdown strength of the polymer matrix for enhanced dielectric performance. Although higher discharged energy densities have been reported for numerous polymer nanodielectrics, the dielectric loss mechanisms, which are extremely important for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
192
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 78 publications
(191 reference statements)
5
192
0
Order By: Relevance
“…However, the dielectric permittivities of polymer dielectrics are usually very low (below 10 @1 kHz), which greatly hindered their wide applications. Toward this end, two strategies have been developed to improve the dielectric constants of polymer composites: (1) ceramic-polymer composites composed of high-k ceramic fillers (e.g., BaTiO 3 [23][24][25][26][27], TiO 2 [28,29], SrTiO 3 [30]) dispersed in polymer matrix and (2) conductor-polymer composites consisting of conductors (e.g., metals, [31,32], graphite [33,34], carbon nanotube [35][36][37], graphene [38,39], carbon black [40], and conductive polymer [41,42]) dispersed in polymer matrix. For ceramic-polymer composites, the enhancement of permittivity is limited (below 50 @10 kHz) even when the ceramic loading excesses 50 vol%, leading to deteriorated mechanical properties, high loss, and low breakdown strength [43].…”
Section: Introductionmentioning
confidence: 99%
“…However, the dielectric permittivities of polymer dielectrics are usually very low (below 10 @1 kHz), which greatly hindered their wide applications. Toward this end, two strategies have been developed to improve the dielectric constants of polymer composites: (1) ceramic-polymer composites composed of high-k ceramic fillers (e.g., BaTiO 3 [23][24][25][26][27], TiO 2 [28,29], SrTiO 3 [30]) dispersed in polymer matrix and (2) conductor-polymer composites consisting of conductors (e.g., metals, [31,32], graphite [33,34], carbon nanotube [35][36][37], graphene [38,39], carbon black [40], and conductive polymer [41,42]) dispersed in polymer matrix. For ceramic-polymer composites, the enhancement of permittivity is limited (below 50 @10 kHz) even when the ceramic loading excesses 50 vol%, leading to deteriorated mechanical properties, high loss, and low breakdown strength [43].…”
Section: Introductionmentioning
confidence: 99%
“…[24,33,34] Although enhanced apparent dielectric constants and increased discharge energy density are reported, the fundamental understanding of dielectric loss mechanisms in polymer nanodielectrics is just emerging. On the basis of a recent report, [35] dielectric losses of polymer nanodielectrics are closely related to the large contrast in permittivity and conductivity between the nanofillers and the polymer matrix. First, the high permittivity (ε r ) nanofillers tend to increase the local electric field in the polymer matrix, [36][37][38][39] especially between chained or clustered particles, [40] resulting in decreased electrical breakdown strength.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] To reduce the internal electronic conduction loss, unipolar, instead of bipolar, electric poling should be used. [35] Alternatively, highly insulating (conductivity σ <10 -13 S/m) nanoparticles with a high ε r (>100) should be used for polymer nanodielectrics; however, such nanoparticles are yet to be discovered. [35] In this study, we continue to investigate the effect of high aspect ratio nanofiber or nanotube fillers on the dielectric loss mechanisms in polymer nanodielectrics.…”
Section: Introductionmentioning
confidence: 99%
“…37-40 a) In this work, it is demonstrated that MoS 2 -PVDF ferroelectric polymer composites result in a broadband CPZ when they are used to fabricate FOCs. This broadband response results from the cumulative effect of three mechanisms on the composite's electrical properties: Maxwell-WagnerSillars relaxation, 41,42 the frequency-dependent phase angle of MoS 2 [due to its semiconducting nature 43 (see supplementary material Sec. S2, Figs.…”
mentioning
confidence: 99%
“…Sillars relaxation takes place. 41 (2) Dipolar relaxation that takes place at intermediate frequencies due to the lack of the alignment response of the abundant dipoles in the polymer to the polarity change of the applied voltage. 5 Adding more fillers results in shifting of Maxwell-Wagner-Sillars relaxation towards higher frequencies [Figs.…”
mentioning
confidence: 99%